2022
DOI: 10.19181/socjour.2022.28.4.9314
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors as Predictors of Revolutionary Situations: Experience in Quantitative Analysis

Abstract: Although there are plenty of quantitative cross-national analyses on the influence of population age structure on revolutionary risks, there are currently not enough studies that examine its impact on the risks of armed and unarmed revolutions taken separately. Assuming that the dependence of potential political destabilization on the median age will differ for armed and unarmed revolutions, we propose the following hypothesis. High median age and the level of a country’s economic development will negatively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…It has also been found that the size of the population itself is a powerful predictor of both revolutionary events in general (Besançon, 2005;Butcher & Svensson, 2016;Chenoweth & Ulfelder, 2017;Dahl et al, 2021;Ustyuzhanin, Zhodzishskaya et al, 2022) and protests in particular (Hegre and Sambanis 2006;Romanov et al, 2021), while anti-government demonstrations are a major component of the revolutionary repertoire of unarmed revolutionary uprisings (Lawson, 2019). This variable is presented in thousands by the Cross-National Time-Series (CNTS) Data Archive (Banks & Wilson, 2021), and we introduce its natural logarithm in order to normalize it and to understand how the difference in population affects not in thousands, but in orders of magnitude.…”
Section: Independent Variable and Controlsmentioning
confidence: 99%
“…It has also been found that the size of the population itself is a powerful predictor of both revolutionary events in general (Besançon, 2005;Butcher & Svensson, 2016;Chenoweth & Ulfelder, 2017;Dahl et al, 2021;Ustyuzhanin, Zhodzishskaya et al, 2022) and protests in particular (Hegre and Sambanis 2006;Romanov et al, 2021), while anti-government demonstrations are a major component of the revolutionary repertoire of unarmed revolutionary uprisings (Lawson, 2019). This variable is presented in thousands by the Cross-National Time-Series (CNTS) Data Archive (Banks & Wilson, 2021), and we introduce its natural logarithm in order to normalize it and to understand how the difference in population affects not in thousands, but in orders of magnitude.…”
Section: Independent Variable and Controlsmentioning
confidence: 99%